2021
DOI: 10.1044/2021_ajslp-20-00401
|View full text |Cite
|
Sign up to set email alerts
|

Shared Interactive Book Reading Interventions for Young Children With Disabilities: A Systematic Review

Abstract: Purpose Shared interactive book reading (SIBR) is an evidence-based practice for young children who are typically developing and those with developmental disabilities or considered at risk for developmental delays. The purpose of this review was to provide a comprehensive examination of the evidence of using SIBR to facilitate growth in language skills for young children with developmental disabilities and/or delays. Specifically, authors examined the descriptive characteristics, study rigor, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…In a review of recent literature, Toews and colleagues (2021) found evidence that shared reading instruction supported comprehension, vocabulary, and early literacy skill development for students with extensive support needs. Other sources have recommended shared reading instruction as a tool for developing expressive language (Towson et al, 2021) and for maintaining heritage languages and extending concepts across languages (Fundelius et al, 2023). With the increased availability of bilingual texts and the whole group style of instruction, educators can take steps before, during, and after shared reading instruction to plan inclusive lessons that strengthen language and comprehension skills in MLs who use AAC.…”
Section: Designing Inclusive Shared Reading Instructionmentioning
confidence: 99%
“…In a review of recent literature, Toews and colleagues (2021) found evidence that shared reading instruction supported comprehension, vocabulary, and early literacy skill development for students with extensive support needs. Other sources have recommended shared reading instruction as a tool for developing expressive language (Towson et al, 2021) and for maintaining heritage languages and extending concepts across languages (Fundelius et al, 2023). With the increased availability of bilingual texts and the whole group style of instruction, educators can take steps before, during, and after shared reading instruction to plan inclusive lessons that strengthen language and comprehension skills in MLs who use AAC.…”
Section: Designing Inclusive Shared Reading Instructionmentioning
confidence: 99%
“…Importantly, the benefit of engaging in shared book reading activities with a wide range of children is also well established, including young children with disabilities (Towson et al, 2021). Most research including children with disabilities has established benefits of shared reading with children with a language disorder or low language skills (Lonigan & Whitehurst, 1998).…”
Section: Overview Of Shared Book Readingmentioning
confidence: 99%
“…Storytime in educational settings often stops with giving children a quick peek into the illustrations, whereas shared book reading is more interactive and can enhance engagement between the adult and child (Towson et al, 2021). Teachers can use the UDL framework in instructional planning to increase student benefits by combining listening to the written word with active engagement with the story (Chen & Dote-Kwan, 2021; Gauvreau et al, 2021).…”
Section: Literacy-based Activities In Preschoolmentioning
confidence: 99%